Sistem Penunjang Keputusan Penyeleksian Penerimaan Karyawan Baru Menggunakan Metode Profil Matching - Julminggu J. Selly (Peneliti.net, 2021)
The selection process in recruitment still have a problems, practically there are some employees who do not really know what they do, that is making the operations do not run smoothly. In addition the number of applicants that is making the relevant sections require a long time in considering candidates who will be accepted. In a computer science there is a system which can help the decision makers to address the problems that are semi structure or unstructured namely the decision support system. In the Decision Support System there are various methods, one of which is a Profile Matching method. This method can assist in determining the priority of multiple criteria to do an analysis of each of the criteria that have been determined. By looking at existing problems in decision-making in recruitment, decision support systems using the Profile Matching deemed appropriate for use in aiding decision making. Expected results of this research can help decision makers in determining acceptance of new employees